Financial Globalization, Portfolio Diversification, and the Pattern of International Trade - Koren, Miklos (Washington, D.C. : International Monetary Fund, 2003)
The paper provides a general-equilibrium model where incomplete international financial markets lead to insufficient industrial specialization and low international trade. As international portfolio diversification is limited and productivity is uncertain, investors wish to maintain a diversified industrial structure rather than specializing according to their comparative advantage. Financial globalization then induces more specialization and more trade. The present framework yields explicit closed-form solutions for the volume and the structure of trade. Empirical results support the implications of the theory. Trade in financially open countries is (i) higher, (ii) more dependent on productivity differences, and (iii) less sensitive to industry risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet